DOI: HTTPS://DOI.ORG/10.36873/AE , RERI YULIANTI*, YANCILUK, SANTOSA YULIANTO, PENYANG, ERWYN: PARTISIPASI PEMILIK LAHAN DALAM PROGRAM PEMBASAHAN BRG MELALUI PEMBUATAN TABAT DI KELURAHAN KALAWA KALIMANTAN TENGAH LAND OWNERS PARTICIPATION IN BRG REWETTING PROGRAM THROUGH CANAL BLOCKING IN KELURAHAN KALAWA CENTRAL KALIMANTAN - Agrienvi (Agrienvi, Jurnal Ilmu Pertanian, 2019)
ABSTRACTRewetting program especially canal blocking (tabat) carried out by the Peat Restoration Agency (BRG) in 2017 aspart of efforts to control forest and land fires that often hit peatlands including in Kalawa Village in 2014 and 2015. Theresults of this study indicate that 7 indicators from 3 research variables for the level of land owners participation in thegroup receiving the rewetting program shows 14.28% has very strong/very high correlation (design making/constructionmodel), 42.86% has strong/high correlation (frequency of socialization, numbers of attendance, socialization method),42.86% has strong enough/high enough correlation (distance of land, placement of position/location, numbers of canalblocking). Whereas for 9 indicators from 4 research variables, the level of land owners participation in the group rejectingthe rewetting program shows 22.22% has strong/high correlation (age, land area), and 77.78% has quite strong/highenough correlation (level of education, distance of land, frequency of socialization, number of attendance, method ofsocialization, construction design/modeling, placement of position/location of canal blocking). The level of land ownersparticipation in the BRG rewetting program through canal blocking (tabat) was dominated by the medium category (36.0%)for the group receiving the program and the low category (48.0%) for the group rejecting the program. The relatively similarcharacteristics of the two community groups and have a major influence on the level of land owners participation aresocialization efforts (frequency of socialization, numbers of attendance, socialization method), and project implementation(design making/construction model, placement of positions/location of canal blocking).Keywords: participation; land owners; canal blocking (tabat); handel; peatland.